Eradication of Animal Abuse of Cafe Based on the Instruction of The Governor of East Java No.1/INST/2012 - Hermawan, Bagus Augusta; Jufri, Muwaffiq (International Journal of Science and Society, 2024)
Karapan Sapi is known as a cow racing contest on Madura Island, which has a high selling value when the cow wins. Karapan Sapi is internalized in people's lives and requires protection for cows as (living) animals. The aim of this research is to determine the protection of cow race animals from the perspective of East Java Governor's Instruction No. 1/INST/2012. The research method used is normative legal research. The results of this research state that the protection of animals (cows) in the implementation of the Karapan Sapi is regulated in Article 302 of the Criminal Code; Article 66A of the Animal Husbandry and Health Law; and Article 92 letter b PP 95/2012. East Java Governor's Instruction No. 1/INST/2012 in terms of content is quite effective, but not effective enough to completely eradicate violence and mistreatment of cows, because there is still a gap for minor violence to be carried out.